2023
DOI: 10.7717/peerj.15741
|View full text |Cite
|
Sign up to set email alerts
|

Impact of climate change on the geographical distribution and niche dynamics of Gastrodia elata

Abstract: Background Gastrodia elata is widely used in China as a valuable herbal medicine. Owing to its high medicinal and nutrient value, wild resources of G. elata have been overexploited and its native areas have been severely damaged. Understanding the impacts of climate change on the distribution of this endangered species is important for the conservation and sustainable use of G. elata. Methods We used the optimized maximum entropy model to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Environmental conditions are the basis of plant reproduction and critical factors that control seed germination 27 . Environmental factors are the most important factors influencing the growth of G. elata Bl., including altitude and precipitation 28 . Therefore, different regions cultivate G. elata Bl.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental conditions are the basis of plant reproduction and critical factors that control seed germination 27 . Environmental factors are the most important factors influencing the growth of G. elata Bl., including altitude and precipitation 28 . Therefore, different regions cultivate G. elata Bl.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, different regions cultivate G. elata Bl. in different geographical locations and climates 28 , 29 , resulting in different varieties of germination fungus. In the cultivation of G. elata Bl., the commonly used germination fungus includes M. osmundicola and M. dendrobii , but they were all isolated and identified in central and southern China.…”
Section: Discussionmentioning
confidence: 99%
“…Suitable habitats for numerous endangered species are expected to undergo varying degrees of reduction in the future, including Gastrodia elata (G. elata), Cathaya argyrophylla (C. argyrophylla), etc. For instance, Hu's [80] findings demonstrated that the geographical distribution of G. elata would reduce in the future and move towards higher latitude regions. Zhao [81] explored C. argyrophylla and demonstrated that its habitat would be threatened in response to global warming and would decrease evidently.…”
Section: Discussionmentioning
confidence: 99%